A wheelchair by the overboard model: A technological instrument for disabled basketball players - Boccia, S.; Izzo, R.; D'Elia, F.; Fattore, S. (Journal of Human Sport & Exercise, 2019)
The aim of the study is to identify a solution to the preliminary study of normal people's capacity of adjustment on a wheelchair in the context of basketball, a solution that fundamentally would also encourage the performance of people with disabilities. As the difficulties encountered in the previous study were mainly on the sitting and on the thrust of the wheelchair, the introduction of the new technological instrument already presented could be useful and meaningful: a chair characterized by the presence of an engine, like the one that distinguishes the electric skateboards of the new millennium, such as overboard and Segway, which work thanks to the displacement of the centre of gravity. Practically, shifting the weight of the bust in all directions (back, forward, right, left) translocations occur in space. Consequently, all this would not only favour the norm gifted athletes who at first impact have many difficulties in the conduction of the wheelchair, but also those who have more or less serious disabilities (especially people with amputation of the upper limbs). In fact, the presence of motor and sensors that allow to move the wheelchair only with the movement of the body centre of gravity, simplifies the performance of sports and makes it less expensive from the point of view of energy, as there would no longer be the need to have to push the mobile device manually.